2000
DOI: 10.1128/mcb.20.11.3817-3830.2000
|View full text |Cite
|
Sign up to set email alerts
|

Class II Phosphoinositide 3-Kinases Are Downstream Targets of Activated Polypeptide Growth Factor Receptors

Abstract: The class II phosphoinositide 3-kinases (PI3K) PI3K-C2␣ and PI3K-C2␤ are two recently identified members of the large PI3K family. Both enzymes are characterized by the presence of a C2 domain at the carboxy terminus and, in vitro, preferentially utilize phosphatidylinositol and phosphatidylinositol 4-monophosphate as lipid substrates. Little is understood about how the catalytic activity of either enzyme is regulated in vivo. In this study, we demonstrate that PI3K-C2␣ and PI3K-C2␤ represent two downstream ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 70 publications
7
138
1
1
Order By: Relevance
“…PIK3C2A is a protein belonging to the PI3/PI4-kinase family and is believed to play a role in the EGF signaling pathway (Arcaro et al 2000). Moreover, Didichenko et al (2003) showed that H. sapiens PIK3C2A is phosphorylated upon exposure of cells to UV irradiation and is also a target of stress-induced phosphorylation during the G2/M transition of cell cycle by the JNK/SAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3C2A is a protein belonging to the PI3/PI4-kinase family and is believed to play a role in the EGF signaling pathway (Arcaro et al 2000). Moreover, Didichenko et al (2003) showed that H. sapiens PIK3C2A is phosphorylated upon exposure of cells to UV irradiation and is also a target of stress-induced phosphorylation during the G2/M transition of cell cycle by the JNK/SAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting using anti-PI3K-C2␣ antibodies (Arcaro et al, 2000) demonstrated that PI3K-C2␣ is present in chromaffin cell extracts and enriched in the chromaffin granule fraction (Figure 2). In these samples, the anti-PI3K-C2␣ antibody detected a single band with an apparent molecular weight of 200 kDa, further confirming its specificity.…”
Section: Resultsmentioning
confidence: 99%
“…In fibroblasts, PI3K-C2␣ has been shown to be enriched on the TGN and clathrin-coated vesicles (Arcaro et al, 2000). On the TGN, PtdIns3P has been shown to be required for the formation of constitutive transport vesicles (Jones and Howell, 1997).…”
Section: Differential Sensitivity To Pi3k Inhibitors Suggest a Role Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, there is emerging evidence that class II PI3K is a significant producer of PtdIns3P, and class II PI3K holds a wide spectrum of functions ranging from cell signaling, to cell migration and vesicle trafficking. [161][162][163][164][165][166] One hint implying a role of class II PI3K in autophagy was provided by the studies on cell corpse clearance by phagocytosis in C. elegans. 167,168 In this process, autophagy is required for phagosome maturation and clearance of apoptotic cells; most importantly, class II PI3K was identified as a complementary kinase producing PtdIns3P on phagosomes, indispensable for the degradation of cell corpses in C. elegans.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%